Isolation and characterization of secondary metabolites of commonly available averrhoa bilimbi L. - Sakib, Shaikh Adnan; Islam , Mm Towhidul; Haque, Md Enamul (Bangladesh Journal of Botany, 2024)
Averrhoa bilimbi L., locally known as bilimbi, is a medicinal plant well-recognized in Bangladesh for its fruit, Carambola. This study aims to identify novel phytochemical compounds responsible for the health benefits of the plant by analyzing its stem bark. The stem barks were collected, dried, and ground to extract the phytochemicals, which were then analyzed using microbiological, chromatographic, and spectroscopy-based methods. The analysis revealed that the extract contained sitosterone and lupeol. Biochemical characterization demonstrated that the extract has potential antibacterial, antifungal, antioxidant, and cytotoxic properties. Further research is needed to characterize these compounds and determine their full spectrum of efficacy. Bangladesh J. Bot. 53(1): 115-122, 2024 (March)